2020
DOI: 10.1186/s41240-020-00169-4
|View full text |Cite
|
Sign up to set email alerts
|

On-farm evaluation of dietary animal and plant proteins to replace fishmeal in sub-adult olive flounder Paralichthys olivaceus

Abstract: Background: High demand and low supply of fishmeal due to overexploitation of fisheries resources have resulted in a dramatic increase in the price of this ingredient. Olive flounder (Paralichthys olivaceus) commercial feed contains approximately 60% fishmeal and limited success has been achieved in identifying sustainable alternative protein sources for this species. Methods: An on-farm feeding trial was conducted to compare a basal diet containing 65% as the control (CONT) with two experimental diets replaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…However, values of whole-body moisture, crude protein and crude lipid contents showed a tendency to continue to decrease when the fishmeal replacement was increased, taking into consideration that the diets were isonitrogenous and isocaloric. A similar trend in whole-body proximate composition was shown by Choi et al (2020). This could be related to the poor utilization of plant and animal ingredients in this study.…”
Section: Ta B L Esupporting
confidence: 87%
See 2 more Smart Citations
“…However, values of whole-body moisture, crude protein and crude lipid contents showed a tendency to continue to decrease when the fishmeal replacement was increased, taking into consideration that the diets were isonitrogenous and isocaloric. A similar trend in whole-body proximate composition was shown by Choi et al (2020). This could be related to the poor utilization of plant and animal ingredients in this study.…”
Section: Ta B L Esupporting
confidence: 87%
“…The nutrient absorption and fish metabolism are directly influenced by intestinal villi length (Choi et al, 2020;Shi et al, 2017).…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…The EAA pro le of whole body samples of experimental shes showing that lysine, methionine and arginine contents were comparatively lower in CSM incorporated diets than the than 0CSM groups. This result is comparable with Choi et al (2020) in sub-adult olive ounder, Paralichthys olivaceus fed the diet containing FM replaced with either animal proteins or animal and plant proteins revealed that most of the amino acids were not signi cantly changed among the treatments.…”
Section: Discussionsupporting
confidence: 73%
“…Liu et al (2016) reported similarly lower level of cholesterol and LDL content in the pre-adults of grass carp fed with varying levels of CSM. Correspondingly,Choi et al (2020) reported that FM replaced with either animal proteins or animal and plant proteins in sub-adult olive ounder effectively reduced the levels of cholesterol when compared with FM based diet.Serum protein pro le in terms of higher albumin and globulin is a valuable indicator of better health status of sh through enhanced innate immune system function(Liang et al 2018). In the present study, the serum protein pro le did not show signi cant changes among the treatments which indicate that CSM content of experimental diets did not in uenced the health status of snubnose pompano.…”
mentioning
confidence: 95%